Descriptive Epidemiology of Tuberculosis during 2019-2022 in the Working Area of Arjasa Primary Healthcare, Jember Regency - Meilinda Alya’ Putri Haryanik; Adistha Eka Noveyani; Arfiani Meikalynda (Universitas Islam Negeri Sumatera Utara, Medan, 2023)
A person can be infected with tuberculosis (TB) simply by inhaling the bacteria that are spread in the air. Tuberculosis can be fatal for someone if it is not treated immediately, but TB can be cured if you take the medicine properly and correctly. The purpose of this study was to determine the distribution of TB disease based on person, place and time at Arjasa Subdistrict, Jember Regency. The type of research used was descriptive quantitative. This research was conducted at Arjasa Primary Healthcare from January to February 2023. The population and sample in this study were all TB patients at Arjasa Primary Healthcare from 2019 to 2022. The variables in this study were person variables (age, gender, type of TB, treatment status), place (village), time (year), achievement success rate (SR), and achievement case detection rate (CDR). Data analysis is in the form of descriptive analysis and is presented in the form of tables and graphs. Based on the results of the analysis, there is no difference between women and men, the most age is adults, the most type of TB is pulmonary TB, and the most treatment status is cured, based on most places, namely Arjasa Village and Kemuninglor, based on the most time, namely in 2022 as many as 60 people, based on the SR the achievements have decreased and have not reached the target, while the CDR has increased but has not reached the target. It is hoped that the Arjasa Primary Healthcare will improve SR and CDR achievements by involving NGOs related to TB, community leaders, religious leaders, the sub-district government, or the local village government.Keywords: Descriptive Epidemiology, Person, Place, Time,Tuberculosis